1995
DOI: 10.1074/jbc.270.23.14094
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression and Regulation of hsp70 and hsp90 by Phorbol Esters and Heat Shock

Abstract: Human peripheral blood monocytes (PBM) produce superoxide anions (O2-.) by a process involving electron transfer from NADPH to O2, catalyzed by the respiratory burst enzyme NADPH oxidase. We have previously shown that phagocytosis, while activating NADPH oxidase, induced in PBM the synthesis of heat shock (HS) proteins (HSP). The present study was undertaken to establish whether this increase in HSP expression was related to O2-. and/or to classical second messengers such as protein kinase C (PKC). Thus, the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
46
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(47 citation statements)
references
References 32 publications
1
46
0
Order By: Relevance
“…This is in agreement with previous reports showing that the activation of HSF by exogenous oxidants is selective for the type of oxidant used, H 2 O 2 being effective while superoxide was not (35). The fact that superoxide dismutase does suppress HSF activation to a modest degree suggests that a secondary oxidant such as the hydroxyl radical, the formation of which requires both H 2 O 2 and superoxide, may also participate in HSF activation.…”
Section: Fig 1 Expression Of Rac1n17 Suppresses Hypoxia/reoxygenatisupporting
confidence: 92%
“…This is in agreement with previous reports showing that the activation of HSF by exogenous oxidants is selective for the type of oxidant used, H 2 O 2 being effective while superoxide was not (35). The fact that superoxide dismutase does suppress HSF activation to a modest degree suggests that a secondary oxidant such as the hydroxyl radical, the formation of which requires both H 2 O 2 and superoxide, may also participate in HSF activation.…”
Section: Fig 1 Expression Of Rac1n17 Suppresses Hypoxia/reoxygenatisupporting
confidence: 92%
“…Stimulation of synthesis of heat-shock proteins and interleukins in leukocytes under stress factors, such as high temperature, was studied by Pizurki and Polla [23], Jacquier-Sarlin et al [24], and Polla and Cassarizza [25]. These authors have shown in in vitro studies of leukocytes that the increase in temperature to 41˚C causes a 10-fold increase in HSP concentration, which is significantly higher than that observed in the current study [23,24]. However, these experiments were performed in vitro, which makes a direct comparison with these results is impossible.…”
Section: Discussionmentioning
confidence: 99%
“…Heat shock protein is a family of broad spectrum protein expressed in cells during stress and acts as molecular chaperon, which maintains normal conformity of other protein. Jacquier-Sarlin et al (Jacquier-Sarlin et al 1995) reported that HSP70, as well as HSP90 expression might be Fig. 3 a, b and c FACS of HSP70 from CF treated cultured hepatocytes.…”
Section: Discussionmentioning
confidence: 98%